Pancreas and islet morphology in cystic fibrosis: clues to the etiology of cystic fibrosis-related diabetes - Malik, Sarah S.; Padmanabhan, Diksha; Hull-Meichle, Rebecca L. (Frontiers in Endocrinology, 2023)
Cystic fibrosis (CF) is a multi-organ disease caused by loss-of-function mutations in CFTR (which encodes the CF transmembrane conductance regulator ion channel). Cystic fibrosis related diabetes (CFRD) occurs in 40-50% of adults with CF and is associated with significantly increased morbidity and mortality. CFRD arises from insufficient insulin release from β cells in the pancreatic islet, but the mechanisms underlying the loss of β cell function remain understudied. Widespread pathological changes in the CF pancreas provide clues to these mechanisms. The exocrine pancreas is the epicenter of pancreas pathology in CF, with ductal pathology being the initiating event. Loss of CFTR function results in ductal plugging and subsequent obliteration. This in turn leads to destruction of acinar cells, fibrosis and fatty replacement. Despite this adverse environment, islets remain relatively well preserved. However, islet composition and arrangement are abnormal, including a modest decrease in β cells and an increase in α, δ and γ cell abundance. The small amount of available data suggest that substantial loss of pancreatic/islet microvasculature, autonomic nerve fibers and intra-islet macrophages occur. Conversely, T-cell infiltration is increased and, in CFRD, islet amyloid deposition is a frequent occurrence. Together, these pathological changes clearly demonstrate that CF is a disease of the pancreas/islet microenvironment. Any or all of these changes are likely to have a dramatic effect on the β cell, which relies on positive signals from all of these neighboring cell types for its normal function and survival. A thorough characterization of the CF pancreas microenvironment is needed to develop better therapies to treat, and ultimately prevent CFRD.